Estilo de vida y riesgo cardiovascular en pacientes con diabetes mellitus tipo 2 - Campos Muñoz, Jesulin Emilio (2020)
Objective: The objective was to identify if there is an association between lifestyle and cardiovascular risk in patients with type 2 diabetes mellitus. Material and methods: Observational, descriptive and correlational study in patients with type 2 diabetes mellitus seen in outpatient internal medicine of the Hospital Regional Docente de Trujillo during April-August of 2017; their lifestyle was determined through the IMEVID questionnaire and cardiovascular risk by the Framingham and UKPDS scores, the latter specific for coronary heart disease. This association was analyzed with the calculation of Pearson's linear correlation coefficient. Results: 114 patients, female gender (64.39%) and mean age of 61.66 ± 13.21 years. Mean lifestyle score by the IMEVID questionnaire of 74.59 ± 15.8 points. The cardiovascular risk per Framingham score was 23.72 ± 15.97% (n = 95), and by the UKPDS score of 14.79 ± 10.08% (n = 110). The analysis of the Pearson correlation coefficient between lifestyle and cardiovascular risk yielded nonsignificant values (p> 0.05), with Framingham (-0.075, 95% CI [-0.272,0.129], p = 0.473) and with the UKPDS (-0.031, 95% CI [-0.217.0.157], p = 0.748). Conclusion: No association between lifestyle and cardiovascular risk was found in patients with type 2 diabetes mellitus.